THE ROLE OF THE GOVERNMENT IN REPRODUCTIVE HEALTH SERVICES FOR ADOLESCENTS WITH MENTAL DISABILITIES IN KUDUS DISTRICT - Indayana Setiawati; Sukma Wardani (LPPM AN NUUR, 2022)
Background: Reproductive health is closely related to public health issues that need attention. Groups with disabilities are often considered to be more susceptible to reproductive risks among other sexual harassment. One of the health problems in disability related to sexual and reproductive health, including the lack of comprehensive knowledge about HIV (Human Immuno Deficiency Virus) and contraceptive knowledge. Preliminary study in Kaliwungu Disabled School Kudus show that students are not fully capable of maintaining reproductive health independently. This study aims to determine the role of government in reproductive health services in adolescents with mental disability in Kudus. Purpose : Knowing the role of the government in reproductive health services for adolescents with mental disabilities in Kudus Regency. Research method: This research uses qualitative descriptive research methods. The subject of this research is the health office of Kudus and Sidorekso Primary Health Care, triangulation of the source in Kaliwungu Disabled Scool Kudus and the parents of the holy Kaliwungu. The Data is subsequently processed and presented in a descriptive form. Result: The role of government in reproductive health services in adolescents with mental disability in Kudus. The government has played a role in accordance with Permenkes 2017 evidenced by the policies and programs of the health Office of Kudus conducted by the Primary Health Care regularly. But in the process of reproductive health services in adolescents with mental disabilities there is no difference with normal teenagers. Conclusion: Based on research that has been done obtained from observations, interviews, and documentation from research subjects and source triangulation was obtained that there was a government role in the reproductive health service in teenagers with mental disabilities in Kudus is a Primary Health Care programs PKPR, which is carried out routinely by Sidorekso Primary Health Care in the form of health counselling in the Kaliwungu Disabled School Kudus